Analysis of Landforms Distribution in Gombe Metropolis, Gombe State, Nigeria - Abashiya, M,; Sule, S, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
This study provides identification and classifications of recent progress in landforms analysis of Gombe metropolis using Geospatial techniques. It focuses on some topographic factors that are important in characterizing the biophysical functions of topography: elevation, contours, topographic position and spatial scale. The Digital Elevation Model (DEM) map showed the three terrain classes as well as their heights, where the least elevation found in areas that includes Bogo, Yelenguruza and Nasarawo with 368m above sea level, with the Liji hills peaking at 670m above sea level. The 10m contour interval clearly differentiated the plains from the highlands with wide and close contour lines respectively. The relief of the metropolis as revealed in conformity with the description that the topography consist of undulating, rugged, and hilly to the southeast and north-eastern part and flat open plains in the central and north-west. The area covers a total of 95.26 square kilometer with 48.08% of plains, 28.74% uplands and 23.18% covered with highlands. However, human activities such as settlements, farming, grazing and mining on the hills and their slopes will continue to modify the topography if not checkmated. The study recommends that human activities on the hills should be well controlled, local communities around the hills or valleys should be educated by the local authority about the dangers associated with their activities. Also more research on automated terrain analysis, especially on the use of topographical features in Gombe metropolis should be carried out.